COMPULSORY ADMINISTRATIVE ACTIONS IMPLEMENTED UNDER THE EMERGENCY EPIDEMIOLOGICAL SITUATION - Margarita Cheshmedzhieva; Antoniya Metodieva (International Journal of Innovative Technologies in Social Science, 2024)
The Article considers the role and meaning of implemented compulsory administrative actions under the emergency epidemiological situation, includes an analysis of legal changes in articles in the law of health about implemented compulsory administrative actions in the whole country or some regions.